Effect of Salinity irrigation water and Selenium spraying in chemical constituents of leaves of Two Cultivars of Okra (Abelmoschus esculentus L. ) Cultivated in Greenhouses - Abbas, Moayed Fadel; Abdullah , Abdullah Abdul Aziz; Hamid, Nadia Nasser (Journal of agricultural, environmental and veterinary sciences, 2018)
Irrigation water salinity at 4 and 8 dSm-1 NaCl caused a significant decrease in Observed a significant decreased in the leaves content of nitrogen as much as 32. 73% and 73. 48% Compared to irrigation RO water, potassium as much as 70. 46% and 89. 08% Compared to irrigation RO water, chlorophylls as much as 44. 61% and 83. 11% Compared to the irrigation at the concentration of 2 dSm-1 and total soluble carbohydrates as much as 62. 12% and 260. 09% Compared to the irrigation at the concentration of 2 dSm-1, However, the same treatment led to a significant increase in the concentration of sodium as much as 88. 75% and 165. 00% and chloride as much as 216. 98% and 354. 08% Compared to irrigation RO water, However, The cv. Al-knissry show up a significant effects in total soluble carbohydrates as much as 3. 48% and potassium as much as 6. 98%, except leaves content of total chlorophylls, sodium and chloride Where the superiority of the cv. Al-batra as much as 1. 36%,14. 46% and 2. 72% respectively. Treatment with selenium at 20 mg. l-1 caused a significant increase in all chemical constituents of leaves decreased depending on the increased concentration of selenium sprayed, except leaves content of sodium and chloride as much as 11. 79% for sodium and 16. 17% for chloride when spraying with concentration 10 mg. l-1 and 72. 39% for sodium and 30. 10% for chloride when spraying with concentration 20 mg. l-1 Compared to the control transaction. The interaction between two or the three factors of the study has a significant effect in all chemical constituents of leaves.
Keywords: okra; salinity; variety; selenium; chemical components